Pregnancy rates in virgin heifers and suckled beef cows after synchronized ovulation using PGF2", norgestomet, and GnRH - Hoffman, D.P.; Krehbiel, C.L.; McKee, R.M.; Stevenson, Jeffrey S.; Nichols, David A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One disadvantage of most estrous synchronization programs is their inability to induce cycling in prepubertal heifers and anestrous suckled beef cows. Suckled cows and virgin heifers were treated with PG F2", norgestomet, and GnRH to induce ovarian cyclicity in prepubertal heifers and anestrous suckled cows as well as to synchronize estrus in cycling females. The treatment consisted of two injections of PGF2" (day –14 and 0) plus 100 μg of GnRH and a 6 mg norgestomet implant on day –7. The implants were removed 24 h after the second injection of PGF2" (day 0). An injection of 100 μg of GnRH was given 30 hours after implant removal. The treatment group was inseminated at estrus or 18 hours after the second injection of GnRH. Pregnancy rate in the treated female s was higher than in the controls that had received PGF injections 14 days 2" apart and were bred at estrus (65.1 vs 48.1%). The treatment also successfully induced a fertile ovulation in previously prepubertal heifers and anestrous cows (treatment vs. control; 67.7 vs 20.0%). We conclude that treating beef cattle with PGF2", norgestomet, and GnRH induced ovarian cyclicity and increased pregnancy rates in prepubertal heifers, anestrus cows, and cycling females.
Keywords: Beef; Prepubertal status; Anestrus; Heifer; Cow; Estrous synchronization